2009
DOI: 10.1159/000212091
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidaemic Pancreatitis Clinical Assessment and Analysis of Disease Severity and Outcomes

Abstract: Introduction: The relationship between pancreatitis and dyslipidaemia is unclear. Patients and Methods: Admissions with acute pancreatitis were prospectively evaluated. A comparison of the demographic profile, aetiology, disease severity scores, complications and deaths was made in relationship to the lipid profiles. Results: From June 2001 to May 2005, there were 230 admissions. The pancreatitis was associated with alcohol (63%), gallstones (18%), idiopathic (9%) and isolated dyslipidaemia (10%). Dyslipidaemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 30 publications
3
58
1
5
Order By: Relevance
“…Therefore, the causes of HTG may be categorized into primary disorders (genetically based) such as lipoprotein lipase (LPL) and apolipoprotein C-II deficiency, which are usually present in childhood as chylomicronemia syndromes, and secondary disorders such as obesity, untreated diabetes mellitus, alcoholism, pregnancy, drugs associated (estrogens, glucocorticoids, and thiazide diuretics) or lithiasis. Abnormalities of insulin responsiveness are present in some of these cases (3,14). The association of SHTG and AP was first postulated by Speck in 1865 (15).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, the causes of HTG may be categorized into primary disorders (genetically based) such as lipoprotein lipase (LPL) and apolipoprotein C-II deficiency, which are usually present in childhood as chylomicronemia syndromes, and secondary disorders such as obesity, untreated diabetes mellitus, alcoholism, pregnancy, drugs associated (estrogens, glucocorticoids, and thiazide diuretics) or lithiasis. Abnormalities of insulin responsiveness are present in some of these cases (3,14). The association of SHTG and AP was first postulated by Speck in 1865 (15).…”
Section: Discussionmentioning
confidence: 96%
“…SHTG is reported to account for up to 10% of all AP episodes (16). It is generally believed that TG levels of >1000 mg/dl are a greater risk factor for AP (3). This threshold is arbitrary and the level above which AP might occur is actually unknown (4).…”
Section: Discussionmentioning
confidence: 99%
“…Atlikta fibrogastroduodenoskopija, išvada: tulžies refliukso požymiai, eriteminė gastropatija, eriteminis duadenitas (galima reakcija dėl kasos patologijos). Kraujo tyrimai: padidėjęs amilazės (672 U/l) ir lipazės (824 U/l) aktyvumas, hiperglikemija (17,28 mmol/l), CRB 415,79 mg/l, ALT, AST ir kreatinino kiekis neišmatuojami dėl ryškios hiperlipemijos (++++). Šlapimo tyrimas: gliukozė šlapime 28 mmol/l, ketonai šlapime 5 mmol/l (++).…”
Section: Klinikinis Atvejis 39 Metų Moteris Turinti Nedidelį Antsvorunclassified
“…HTG diagnozuojama, kai TG kiekis kraujyje yra >1,69 mmol/l (150 mg/dL), sunki -daugiau kaip 22,6 mmol/l (2000 mg/dL) [19]. Vien pirminė HTG (šeiminė, genetiškai nustatyta) yra reta HP priežastis [17][18]. HP savarankiškai gali sukelti I dislipidemijos tipas (šeiminė chilomikronemija; paveldima autosominiu recesyviniu būdu) pagal Fredrickson'o klasifikaciją (HTG -dėl lipoproteinlipazės ir apolipoproteino C-II defekto), kuris dažniausiai diagnozuojamas ankstyvoje vaikystėje ir yra labai retas (1/1000000).…”
Section: Klinikinis Atvejis 39 Metų Moteris Turinti Nedidelį Antsvorunclassified
“…It was also observed that adverse outcomes in patients with dyslipidemia were seen in hypertriglyceridemia, even though past studies did not see this relationship. 39,40 In cases of acquired hypertriglyceridemia, patients with a pre-existing lipid abnormality can develop pancreatitis in the setting of a secondary factor such as poorly controlled diabetes, alcohol use, or intake of medication such as estrogens and beta-blockers. 37 Control of triglyceride levels can prevent additional attacks of pancreatitis, specifically if levels are less than 1000 mg/dL.…”
Section: Dyslipidemiamentioning
confidence: 99%